About the Term “Commenced Performance” (Used in Art. 308 of the Commerce Act) Regulating the Earnest Money Institute - Vangelova, Zlatka (Research Papers, 2021)
The legal literature does not interpret uniformly the final moment when a party of a contract may back out of it. Under one of the expressed opinions this is the moment of commencement of the factual performance, while, under the second opinion, this is the maturity date of the obligation for performance of any of the parties in the contract. The second opinion is supported in this report and arguments are presented in its favour.
Keywords: Back out of a contract; Earnest money; Liquidated damages; Maturity date; Default